Scheme on user identity attribute preserving based on ring signcryption for cloud computing - Shuan-bao LI; Jian-ming FU; Huan-guo ZHANG; Jing CHEN; Jing WANG; Bi-jun REN (Tongxin xuebao)
Identity attribute leak as the most severe security threat of cloud computing,in order to solve this problem,a protection scheme of identity attributes based on ring signcryption was proposed.Focused on digital identity management in cloud service,which discusses user key parting management with decentralization.Users can choose some seeds for generation and storage of key,then integrated user key cannot be acquired by registrar,based on this payload on certifica-tion management is reduced.In addition,access-centric blindness ring signcryption verification for identity attribute is designed,which constitutes ring of users and CSP,combined with own attribute users can accomplish ring-oriented sub-linear blindness signcryption and non-interactive public ciphertext verifiability for messages so that integrity and confidentiality of identity attribute can be protected avoiding identity attribute leakage in collusion of multi-CSP.At last,strong blindness and unforgeability of ciphertext and attribute is proved in proposed model,three private key components can be generated by users and identity forgeability of ring member can be prevented successfully on the condition of DBDH difficult assumption and adaptive chosen-ciphertex tattacking.Effectiveness of proposed mechanism is verified via performance evaluation of blindness ring signcryption algorithm based on comprehensive payload in identity attribute protection,and optimization is confirmed compared with similar algorithms.